PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI PADA KANTOR CAMAT TELUKDALAM - Bobby Candrasman Gowasa (Jurnal Ilmiah Mahasiswa Nias Selatan, 2026)
The purpose of this study was to determine the effect of organizational culture on employee performance at the Telukdalam sub-district office. This type of research is a causal qualitative research. The sample in this study were all employees at the Telukdalam sub-district office with a total population of 31 employees. The analytical method used in this research is simple linear regression analysis. The results of this study indicate that organizational culture variables have no effect on employee performance at the Telukdalam sub-district office, South Nias Regency. In this study, a simple linear regression equation was obtained, namely: Y = 0.46 + 0.68X and a tvalue of 0.249 was obtained which was smaller than the ttable 2.045 because the tvalue (0.249) < ttable (2.045) organizational culture had an effect on employee performance but the effect is very small. Furthermore, the calculated significance value is 0.805 > 0.05 alpha level, because the calculated significance value is > 0.05, organizational culture has no significant effect on employee performance.